Argentina : Request for Stand-By Arrangement-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
Despite a difficult economic context, President Macri's administration, over the past two and a half years, has taken bold steps to eliminate a wide range of distortions in the economy. Efforts were also made to strengthen institutions (including the complete reconstruction of the statistics agency, in an effort to restore credibility to Argentine data), as well as an assertive effort to tackle corruption. Despite these efforts, a gradual approach to fiscal consolidation, combined with a tightening of global financial conditions, a poor harvest, and the introduction of a tax on nonresident holdings of short-term central bank paper, generated significant anxiety among market participants. Starting in mid-April, Argentina came under abrupt balance of payments pressures as both domestic and foreign investors decided to liquidate their position in onshore peso assets. To stem the outflows, the authorities significantly increased short-term interest rates, tightened fiscal policy, and sold foreign exchange. Shortly after taking these steps the government announced its intention to approach the IMF for an exceptional access Stand-By Arrangement.